Highly Conductive Copper Film on Inkjet-Printed Porous Silver Seed for Flexible Electronics. Issue 5 (1st January 2018) - Pandey, Richa; Friedberg, Stav; Beggiato, Matteo; Sverdlov, Yelena; Lishnevsky, Katya; Demarchi, Danilo; Shacham-Diamand, Yosi
Abstract : Material properties of electroless deposited copper film suitable for electronic circuits have been studied on Silver nanoparticle inkjet-printed polyimide substrate. The optimized process includes silver nanoparticle seed printing, sintering at 300°C, followed by electroless deposition. The result was a highly conducting copper metallization with an improved resistivity of 2.1μΩ.cm compared to only printed silver. We also present composition analysis by XPS and structural characterization by FIB-SEM and profilometry. FIB-SEM, XPS, and XRF were integrated together to deduce the kinetics of electroless deposition on the highly porous silver nanoparticle seed. The results and the model indicate that the copper deposition is in two consecutive stages: (a) copper deposited inside the seed silver layer to fill the porous channels formed after annealing (b) the copper deposited uniformly on top of the filled pores. The effective conductance is a result of the two elements, silver and copper, the composite formed in the seed and the dense polycrystalline copper thin film deposited on the top of the seed.